Rabbit Angiotensin-converting Enzyme-2: 3D Structural Reconstruction and Comparison with its Human Analog - Svetlana H. Hristova; Trifon T. Popov; Alexandar M. Zhivkov (Chemistry and Biochemistry: Research Progress Vol. 5, 2025)
The transmembrane glycoprotein angiotensin-converting enzyme-2 (ACE2), currently better known as the receptor for the coronavirus S-protein, has a key role in blood pressure regulation in humans and mammals. The polypeptide chain of ACE2 has two segments, which form a large globular hydrophilic domain with carboxypeptidase catalytic activity, and a small hydrophobic transmembrane collectrin-like segment. To explain on a molecular level the association of the S protein to ACE2 when using rabbits as an animal model for studying the coronavirus infection, it is needed to know the 3D structure of the rabbit protein rACE2. The aim of the research is to reconstruct the 3D structure of the catalytic domain of rACE2 using its human analog hACE2 as a model, considering the differences in the primary amino acid sequences of the two enzymes, which have a high identity: 85%. Tertiary structure alignment of rACE2 and hACE2 catalytic domains discloses a coincidence in the \(α\)-helix segments, with minor deviations in two unstructured sections of the polypeptide chains. The pH dependences of the electrostatic component of the free energy of the two proteins have similar courses, but the 3D structure of the rabbit analog is somewhat more stable. The significant resemblance in the structure and thermodynamic properties between rACE2 and hACE2 suggests that rabbits can serve effectively as animal models for investigating blood pressure regulation and coronavirus infection, with the findings extrapolable to humans.